REGULASI MAKANAN HALAL DI INDONESIA - Siradjuddin, Azmi (JURNAL TAPIS, 2013)
Indonesia has Â the biggest muslim countries among other muslim countries Â all over the world. Therefore the Indonesian government must protect for Indonesian food of Halal or it is called Halal Food (Allowed). The word of halal is derivated from Arabic language, in Islam means âallowedâ. The term od halal is often mentioned in our life of some food and drink . Those food and drink are allowed according to Islamic law as written in the holy Qurâan. Therefore the Indonesian government and Indonesian Ulama Board must protect by the regulation all food and drink in other tobe safety in their life . It is very worst when there is not mutual undertanding to protect the muslim people eirther in food or other products. It is needed theÂ  âCertificate of Halalâ and Must be given to the Indonesian muslim for their safety in their life. All the product halal must be checked and examined by LPPOM MUI. So in 1989 the Indonesian Ulama Board has established LPPOM MUI and in 1991 by the Presidentâs instruction number 23, 1999 and it is coordinated by Minester of welfare together MUI. Thus in 1992 by Constitution number 23, 1992, the problem of muslimâs food and drink can be protected by the above regulation. Based on the above regulation so the Minister of health has the authority to do the supervision of the halal product either food or drink and all products. In 1996 by the constitution number 7, 1996 The Minister of health strickly confirms about âfoodâ that all the products come either from Indonesia or from other countries must give âthe lable of halalâ and it is the decition of Minester of health number 83/Menkes/SK/VII/1996. The protection of the cunsumen must be continous forever to reaching happiness, accuracy, goodness in their life of social climate in this case the âconstitutionâ of halal food must be Â concepted continously in every field of products and to be controlled by LPPOM-MUI and Indonesia legislative assembly DPR).Keyword: Halal lable, ethics and Halal food.Â